IDENTIFIKASI KANDUNGAN FORMALIN PADA MIE BASAH MENGGUNAKAN PEREAKSI SCHRYVER - Nurul Fatimah; Henny Nurhasnawati; Roufida Zaki (jurnal ilmiah manuntung sekolah tinggi ilmu kesehatan samarinda, 2018)
Foods or food ingredients that contain high water content are not durable to store. This trigger manufacturers of small industries and home industries to use additional ingredients such as preservatives. Banned preservatives used in food are formalin. Identification of formaldehyde can be done by color reaction, among others, using Schryver reagent. This study aims to determine the identification of formalin content in wet noodles using Schryver reagent. This research is a type of experimental research. Sample in this research is chicken noodle and meatball noodle which is obtained from seller at Abdul Wahab Syahranie Street. The research stages include sample collection, Schryver reagent manufacture, spike sample preparation and sample testing. Data analysis used in this research use descriptive analysis method. The results of six samples of chicken noodle and meatball noodles located at Abdul Wahab Syahranie Street, that from six samples did not contain formalin. Keywords : wet noodles, formalin, Schryver reagent